Population Dynamics of Shark Species in the Coast Of Ghana, West Africa - Ackah, Rachael; Amekor, William Dzisenu; Amponsah, Samuel KK (Research in Agriculture Livestock and Fisheries, 2023)
This study aimed at assessing the growth and mortality parameters of the Prionace gluaca and Sphyrna lewini shark species from the coast of Ghana. Data was taken for nine (9) months from April 2021 to December 2021. The length data taken from the shark species was analyzed for the estimation of population parameters using the FiSAT II tool. From the results, the estimated asymptotic length (L∞) and the growth rate (K) of P. glauca and S. lewini were 396.4 cm and 0.27 yr–1 and 349.1 cm and 0.24 yr–1 respectively, indicating that these species exhibited slow growing characteristics, evinced by a longevity of approximately 11 – 12 years. The length at first capture (Lc50) for P. gluaca was 128.6 cm and that for S. lewini was 169.0 cm. The length at first maturity (Lm50) for P. gluaca and S. lewini was 179.74 cm and 160.4 cm respectively. By comparing the Lc50 and Lm50, it implies that individuals of P. gluaca were vulnerable to fishing gears before having the chance to mature and even spawn once. The total mortality (Z), natural mortality (M), fishing mortality (F) and the exploitation rates for P. glauca and S. lewini were 0.82 yr–1 , 0.22 yr–1 , 0.60 yr–1 and 0.73 and 0.76 yr–1, 0.21 yr–1, 0.55 yr–1 and 0.72, respectively. This suggests that fishing activities are the main cause of decline in the abundance of these shark species. The exploitation rate (E > 0.5) revealed that these species are overexploited in Ghana’s marine waters. Based on these findings, it is recommended that fishing effort be reduced through appropriate measures by relevant authorities. Vol. 9, No. 3, December 2022: 353-365